The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1128/jb.184.16.4420-4429.2002
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of theStreptomyces lividans ramGenes: Involvement of RamR in Regulation of theramCSABOperon

Abstract: Streptomycetes are filamentous soil bacteria that produce spores through a complex process of morphological differentiation. The ram cluster plays an important part during the development. The ram genes encode a membrane-bound kinase (RamC), a small protein (RamS), components of an ABC transporter (RamAB), and a response regulator (RamR). While the introduction of an extra copy of the ram cluster accelerates development in Streptomyces lividans, ramABR disruption mutants are unable to produce aerial hyphae and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
71
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(79 citation statements)
references
References 39 publications
(53 reference statements)
8
71
0
Order By: Relevance
“…The dots represent sequence gaps between the two orthologous regions. The transcriptional start site of ramC has not been identified in S. coelicolor A3 (2), and the site presented is that determined in S. lividans by Keiser et al (12). The nucleotide sequences of the ramC promoter regions of S. coelicolor and S. lividans are identical.…”
Section: Methodsmentioning
confidence: 67%
See 1 more Smart Citation
“…The dots represent sequence gaps between the two orthologous regions. The transcriptional start site of ramC has not been identified in S. coelicolor A3 (2), and the site presented is that determined in S. lividans by Keiser et al (12). The nucleotide sequences of the ramC promoter regions of S. coelicolor and S. lividans are identical.…”
Section: Methodsmentioning
confidence: 67%
“…Recently, extensive studies by three research teams have shown that the ram gene cluster plays a significant regulatory role in developmental regulation in S. coelicolor A3(2), the best-studied model organism (12,20). They revealed that promoter activities for ramR and ramCSAB, equivalent to amfR and amfTSBA, respectively, are developmentally regulated, and inactivation of either ramR or ramC abolishes aerial growth.…”
mentioning
confidence: 99%
“…Expression of the chaplin genes is developmentally regulated, and their transcription is blocked in all the bld mutants tested, including bldC (19). Expression of the ram genes is also developmentally regulated, and ramR and ramCSAB transcription is blocked in bldA, bldB, bldD, and bldH mutants (bldC has not been tested) (25). Further, almost all bld mutants regain the ability to form aerial structures when purified SapB is applied to the colony surface (51).…”
mentioning
confidence: 93%
“…Conversely, overexpression of ramR results in SapB overproduction and the biosynthesis of SapB by wild-type strains under conditions when its production is normally repressed (38). The ram genes are not transcribed during growth on minimal medium (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation